2015
DOI: 10.1037/cou0000066
|View full text |Cite
|
Sign up to set email alerts
|

Social cognitive predictors of first- and non-first-generation college students’ academic and life satisfaction.

Abstract: The present study tested Lent's (2004) social-cognitive model of normative well-being in a sample (N = 414) of first- and non-first-generation college students. A model depicting relationships between: positive affect, environmental supports, college self-efficacy, college outcome expectations, academic progress, academic satisfaction, and life satisfaction was examined using structural equation modeling. The moderating roles of perceived importance of attending college and intrinsic goal motivation were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 36 publications
11
77
2
1
Order By: Relevance
“…Previous studies have found that students who report higher levels of interaction with supportive faculty as mentors and advisors also tend to report higher levels of academic and college self-efficacy (Santos & Reigadas, 2002;Vogt, 2008). Furthermore, in studies with diverse college students, academic self-efficacy mediated the relation of faculty-student interactions to college grades (DeFreitas & Bravo, 2012); college self-efficacy also mediated the relation of environmental supports to self-perceived academic progress (Garriott et al, 2015). These findings suggest that consistent with Bandura's theory, formal and informal interactions with supportive others, including faculty, may provide opportunities for students to receive encouragement regarding their ability to succeed in college related tasks as well as opportunities to learn from faculty mentors how to navigate the college experience.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have found that students who report higher levels of interaction with supportive faculty as mentors and advisors also tend to report higher levels of academic and college self-efficacy (Santos & Reigadas, 2002;Vogt, 2008). Furthermore, in studies with diverse college students, academic self-efficacy mediated the relation of faculty-student interactions to college grades (DeFreitas & Bravo, 2012); college self-efficacy also mediated the relation of environmental supports to self-perceived academic progress (Garriott et al, 2015). These findings suggest that consistent with Bandura's theory, formal and informal interactions with supportive others, including faculty, may provide opportunities for students to receive encouragement regarding their ability to succeed in college related tasks as well as opportunities to learn from faculty mentors how to navigate the college experience.…”
Section: Discussionmentioning
confidence: 93%
“…Results of a meta-analytic study showed that self-efficacy beliefs were positively related to students' academic attainment and persistence attitudes across a wide variety of fields (Multon, Brown & Lent, 1991). More recent studies also have reported a positive relation of college self-efficacy to students' college satisfaction, academic performance and expectations of persistence to graduation (DeWitz, Woolsey, & Walsh, 2002;Garriott, Hudyma, Keene & Santiago, 2015;Vuong, Brown-Welty, Tracz, 2010) including students of Hispanic descent (Gloria, Castellanos, Lopez, & Rosales, 2005;Ojeda, Flores, & Navarro 2011;Torres & Solberg, 2001). …”
Section: Self-efficacymentioning
confidence: 99%
“…Their findings also suggested that by lowering perceived stress and increasing coping resources, clients' sense of life satisfaction could be substantially improved. In another study, Garriott, Hudyna, Keene, and Santiago () used Lent's () hypothesized model of normative well‐being to predict academic and life satisfaction among first‐ and non‐first‐generation college students. They found that college self‐efficacy predicted academic progress, whereas academic satisfaction (but not academic progress) predicted life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of recent college graduates indicated that about a third of students obtained an internship or job related to their major through a professor (Gallup Inc., ). More generally, studies demonstrate that supportive interactions with faculty both in and outside of the classroom contribute to students’ retention, academic success, and general well‐being (Deil‐Amen, ; Garriott, Hudyma, Keene & Santiago, ; Ishitani, ; Padgett, Johnson & Pascarella, ; Umbach & Wawrzynski, ; Woosley & Shepler, ). Stanton‐Salazar () also described the importance of connections with institutional agents, or those in key positions to facilitate access to services, opportunities, and resources, especially for lower status students who may be less likely to have such access.…”
Section: Introductionmentioning
confidence: 99%